Estudo das características de materiais magnéticos aplicados ao acionamento de lâmpadas fluorescentes sem eletrodos - Chagas, Natalia Braun (2014)
This paper presents a study of the characteristics of magnetic materials. The application of this study is the feeding of an electrodeless fluorescent lamp (EFL). This type of lamp is driven by electromagnetic effects and, because of this, the electrodes are eliminated. Thus, the EFL has longer lifetime associated with low lumen depreciation representing an alternative to lighting systems among other discharge lamps. Because of the EFL magnetic characteristics, the operation frequency of this type of system has to be high in order to reduce the size of inductive elements avoiding the shadowing. Thus, the study of different magnetic materials capable of operating under these circumstances is proposed. Experiments were performed in order to obtain material characteristics such as the magnetization curve and the energy losses, and simulations were used to study characteristics not available through practical means. Four different materials are analyzed, the ferrites N87 (from EPCOS) and IP12E (from THORNTON) and amorphous and nanocrystalline alloys. In the ferrites cases, it was possible to carry out practical experiments and prove that they are able to meet the operating needs of EFL. However, it was not possible to acquire toroids alloys, amorphous or nanocrystalline, with the internal diameter required to accommodate the bulb of the EFL therefore, results of simulations are presented for these cores projects. At the end of the work, comparisons are made between the results obtained.